Efficacy of acetic acid vapours and dry heat to control Fusarium graminearum and Bipolaris sorokiniana in barley and wheat seeds - Rioux, Sylvie; Pouleur, Stéphan; Randall, Paul; Vanasse, Anne; Turkington, T.; Dion, Yves; Belkacemi, Khaled (Phytoprotection, 2016)
To find seed treatments that are acceptable for organic cereal production, we tested the efficacy of three treatments, i.e. dry heat, a low dose of acetic acid vapours (AAV-L), and a high dose of AAV (AAV-H), to control Fusarium graminearum (Fg) and Bipolaris sorokiniana (Bs), two seed-borne pathogens affecting emergence and yield in barley and wheat. These treatments were compared with a control (no treatment) and Vitaflo®-280. Treatments were applied on six barley and six wheat seed lots contaminated with Fg at a rate of > 20% (i.e. > 20% of seeds contaminated) and/or Bs at a rate of > 50%. For all Fg-contaminated lots, the three non-chemical treatments reduced the contamination rate under the rejection threshold of 15%, which is the Danish recommendation for Fusarium spp. For Bs-contaminated lots, AAV-H reduced contamination the most, followed by AAV-L, and then by dry heat, which had no effect on barley. However, these treatments did not reduce Bs contamination under the rejection threshold of 30%, except for AAV-H in one barley lot and dry heat in one wheat lot. Also, AAV-H reduced the germination in three wheat lots and in the hulless barley AC Hawkeye, and this had negative effects on grain yield for two of the wheat lots. AAV-H had no effect on grain yield in the other lots, and neither did the other treatments in any of the lots. Dry heat was effective for controlling Fg in both cereals, whereas AAV-H showed some potential to control both pathogens, but only in covered grains. None of the treatments evaluated appears to be appropriate for reducing contamination by either pathogens in wheat and barley.